(untitled) (Sociología y tecnociencia, 2024)
The development and use of the artificial intelligence (AI) has exponentially grown in last years, populating many relevant and diverse fields, and consequently entering into the society and the collective behaviour of its citizenship. However, its key role seems to be still not fully appreciated by the individuals, even being sometimes misinterpreted or underrated. Hence, we review in this work the origin and definition of AI, some of its currently most prominent examples of field of applications, its environmental impact, as well as drop some suggestions for future questions in further and detailed social pools about AI.